Lentiviral-Engineered Mesenchymal Stem Cells for Hemophilia B Gene Therapy - Dodd, Megan J. (My University, 2013)
Hemophilia B patients may have frequent, spontaneous and life-threatening bleeds that are currently managed by an invasive and expensive treatment. Mesenchymal stem cells (MSCs) are increasingly being applied to clinically therapeutic strategies and lentiviral gene vectors have been shown to be safe and efficient tools for modifying stem cells for long-term expression of high levels of transgenes. In this study, MSCs were engineered with a lentivirus to express sustained and therapeutic levels of human FIX protein in vitro and in mice. The modified MSCs secreted human FIX protein at levels exceeding 4 μg/106 MSCs/24 h with high FIX coagulant activity of greater than 2.5 mIU/106 MSCs/24 h for 6 week in vitro. Functional FIX transgene was continually expressed by these cells when they were induced to differentiate into adipocyte, osteoblast and chondrocyte lineages in vitro. However, the modified MSCs transplanted via tail vein into NOD-SCID-γ mice expressed low levels of FIX in vivo. The transplantation procedure had an increased risk of death that was more pronounced in mice that received cell doses exceeding 2 million cells. Organ examinations suggested the deaths resulted from entrapment of MSCs in pulmonary capillaries. Modified MSCs encapsulated in alginate-PLL microcapsules and transplanted into the peritoneal cavity of both NOD-SCID-γ and hemophilia B mice at 9 million cells/mouse resulted in therapeutic expression around 100 ng of human FIX/mL of plasma only for a few days in vivo as human FIX expression quickly decreased to basal values by the end of the first week. Cultured ex vivo, human FIX expression by retrieved capsules indicated an innate immune response to the encapsulated cells prevented sustained expression of FIX. These investigations demonstrate that lentivirally modified MSCs have the potential to express therapeutic human FIX for sustained periods in vitro, even after their differentiation. However, they also highlight the challenges to overcome to optimize cell engraftment and survival following transplantation, and to minimize the immune responses associated with the xenogeneic translational models used.
Keywords: gene therapy; hemophilia; mesenchymal stem cell; Factor IX; lentivirus; differentiation; alginate; translational; Molecular, cellular, and tissue engineering; Molecular, cellular, and tissue engineering